2022
DOI: 10.21203/rs.3.rs-1434398/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thalamic and medial prefrontal cortical circuits mediate social defeat stress-induced depression-like behaviors

Abstract: The mediodorsal thalamus (MD) is interconnected with the medial prefrontal cortex (mPFC) and works together to promote some forms of behavioral flexibility. But the relationship between the MD-mPFC circuit and depression is remain unknown. Here, we show that in male susceptible mice, MDGLU neuronal calcium signaling activity is reduced. Chemogenetic inhibition of MDGLU neuronal in male C57BL/J mice resulted in behavioral abnormalities, whereas in susceptible mice, activation of MDGLU neuronal ameliorated depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(55 reference statements)
0
0
0
Order By: Relevance
“…Social experiences create memories that enable individuals to categorize subsequent social encounters as either threatening or safe, thereby eliciting appropriate behaviors to achieve specific goals [11][12][13][14][15][16]. Prior studies have shown that multiple brain regions signal distinct socially motivated behaviors; for example, the ventromedial hypothalamus (VMH), medial amygdala (MeA), and the bed nucleus of stria terminalis (BNST) are implicated in promoting aggression and defensive responses [17][18][19][20][21][22], while the nucleus accumbens (NAc), medial preoptic area (mPOA), and ventral tegmental area (VTA), among others, facilitate social interactions [10,16,[23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Social experiences create memories that enable individuals to categorize subsequent social encounters as either threatening or safe, thereby eliciting appropriate behaviors to achieve specific goals [11][12][13][14][15][16]. Prior studies have shown that multiple brain regions signal distinct socially motivated behaviors; for example, the ventromedial hypothalamus (VMH), medial amygdala (MeA), and the bed nucleus of stria terminalis (BNST) are implicated in promoting aggression and defensive responses [17][18][19][20][21][22], while the nucleus accumbens (NAc), medial preoptic area (mPOA), and ventral tegmental area (VTA), among others, facilitate social interactions [10,16,[23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%